Experimental analysis on physical and mechanical properties of thermal shock damage of granite (Fracture and Structural Integrity, 2016)
The purpose of this study was to explore the changes of mechanical and physical properties of granite under different thermal loading effects. Uniaxial compression experiments studying the rules of the influence of temperature load on mechanical properties of granite were carried out. After high-temperature heating at above 600 °C, granite tended to have stronger ductility and plasticity as well as declined peak stress and compressive strength. Thermogravimetry - differential scanning calorimetry (TG-DSC) analysis results showed that, thermal load at different temperatures induced reactions such as water loss, oxidation and crystallization in the microstructure of granite, which led to physical changes of granite. Hence it is concluded that, heating can significantly weaken the mechanical performance of granite, which provides an important support for the optimization of heating assisted processing of granite. It also reveals that, heating assisted cutting technique can effectively lower energy consumption and improve processing efficiency.
Keywords: Granite; Damage; Differential scanning colorimetry analysis; Uniaxial compression thermogravimetry analysis